Pengaruh Pelatihan Kerja, Pengalaman Kerja dan Locus Of Control Terhadap Kinerja Karyawan Pada Pd. BPR BKK Kabupaten Tegal - Santika, Nofia Dwi; Prihadi, Deddy (Major Management, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2021)
This study aims (1) to determine the effect of job training on the performance of PD.BPR BKK employees in Tegal Regency (2) to determine the effect of work experience on the performance of PD.BPR BKK employees in Tegal Regency (3) to determine the Locus Of Control on the performance of PD employees. BPR BKK Tegal Regency (4) To determine the simultaneous effect of Job Training, Work Experience and Locus Of Control on Employee Performance PD.BPR BKK Tegal Regency. This research is categorized as survey research, where the research instrument is a questionnaire and uses a Likert scale. The population in this study were all employees of PD.BPR BKK Tegal Regency totaling 60 people. The samples taken in this study were all of the population (saturated samples), namely 60 respondents. Test the validity of this instrument using the product moment correlation technique at a significant level of 5% (0.05) with degrees of freedom r table = 0.254 (N = 60). While the reliability test uses Cronbach Alpha. The analysis technique used is multiple linear regression. This study shows that all statements in the questionnaire with a total of 29 statements have been valid and reliable, so they can be used. And the results of the R Square test show that the results of R2 = 0.446 means that 44.6% of employee performance (Y) is influenced by the amount of Job Training (X1), Work Experience (X2) and Locus Of Control (X3) the remaining 53.4% influenced by other factors outside the model.